Timing and Duration of Obesity in Relation to Diabetes: Findings from an ethnically diverse, nationally representative sample - The, Natalie S. (American Diabetes Association, 2013)
OBJECTIVE: The influence on diabetes of the timing and duration of obesity across the high-risk period of adolescence to young adulthood has not been investigated in a population-based, ethnically diverse sample. RESEARCH DESIGN AND METHODS: A cohort of 10,481 individuals aged 12–21 years enrolled in the U.S. National Longitudinal Study of Adolescent Health (1996) was followed over two visits during young adulthood (18–27 years, 2001–2002; 24–33 years, 2007–2009). Separate logistic regression models were used to examine the associations of diabetes (A1C ≥6.5% or diagnosis by a health care provider) in young adulthood with 1) obesity timing (never obese, onset <16 years, onset 16 to <18 years, onset ≥18 years) and 2) obesity duration over time (never obese, incident obesity, fluctuating obesity, and persistent obesity), testing differences by sex and race/ethnicity. RESULTS: Among 24- to 33-year-old participants, 4.4% had diabetes (approximately half were undiagnosed), with a higher prevalence in blacks and Hispanics than whites. In multivariable analyses, women who became obese before age 16 were more likely to have diabetes than women who became obese at or after age 18 (odds ratio 2.77 [95% CI 1.39–5.52]), even after accounting for current BMI, waist circumference, and age at menarche. Persistent (vs. adult onset) obesity was associated with increased likelihood of diabetes in men (2.27 [1.41–3.64]) and women (2.08 [1.34–3.24]). CONCLUSIONS: Diabetes risk is particularly high in individuals who were obese as adolescents relative to those with adult-onset obesity, thus highlighting the need for diabetes prevention efforts to address pediatric obesity.